KAJIAN POTENSI BEBERAPA VARIETAS UNGGUL TANAMAN Padi (Oryza sativa L.) BERBASIS VIABILITAS - Rahayu, Sri; Gamawati Adi Nurani, Praptiningsih; Ayu Pranata, Maya (JURNAL AGRI-TEK, 2016)
The community forest plays an important role to reduce greenhouse gas emissions because forests can absorb carbon dioxide in the air which is then storing in the tree. Measurement of the amount of C stored in the body plant life (biomass) in a community forest can describe the amount of CO in the atmosphere is absorbed by plants. Research activities aimed to estimate how much carbon stocks in mahoni trees in public forests certified SVLK (Timber Legality Verification System). The method used is the manufacture destruction allometric equations with the method of mahoni tree species. The location of research conducted in the area of community forests managed by the Forest People’s Association business (PPHR) Lawu Lestari, district Panekan, Magetan. With an area of 192.16 hectares and spread over three (3) villages namely Ngiliran, Jabung and Bedagung and already getting sertivikat SVLK Certification Body PT SGS Indonesia on December 4, 2013. The amount of the percentage of biomass per tree parts from the greatest is the rod 54.07%, 22.02% Branches and twigs, roots 13.21% 10.70% last leaf. Model equation for estimating the amount of carbon content mahogany Y = 48,389 d 2,443 . Keywords: carbon content; mahoni; community forest; wood Legality The research to assess the potential for some superior varieties of rice plants Inpari 33, Inpari 30 Inpari 4, LUK Ulo, Mengkoga, IR 64, Cibogo and Ciherang based on the viability of each variety. Research using design Randomized with eight (8) the treatment of varieties (V) Inpari 33 (V1), Inpari 30 (V2), Inpari 4 (V3), Luk Ulo (V4), Mekongga (V5), IR 64 (V6 ), Cibogo (V7) and Ciherang (V8) and repeated 3 times. The results of the research study showed that rice varieties studied (V) Inpari 33 (V1), Inpari 30 (V2), Inpari 4 (V3), Luk Ulo (V4), Mekongga (V5), IR 64 (V6), Cibogo ( V7) and Ciherang (V8) effect on a number of variables observed were: the number of normal seedling, sprout abnormal number, the number of fresh seeds do not grow, plant height, number of tillers (aged 28, 42, 56 day after planting), and panicle length. These varieties do not affect the variable: the number of dead seeds, number of tillers at the age of 14 day after planting, the number of panicles, number of grains contained, the amount of grain hollow, and the weight of 100 grains.Keywords: potential, improved varieties, viability